2009
DOI: 10.1177/089686080902902s07
|View full text |Cite
|
Sign up to set email alerts
|

Technical Aspects in Studying Peritoneal Morphology in Animal Models of Peritoneal Dialysis

Abstract: Objective Peritoneal biopsies are considered useful for gaining a better understanding of the pathophysiology of the peritoneum during experimental peritoneal dialysis (PD). Different peritoneal tissue samples (i.e., abdominal wall, liver, diaphragm, intestine, and omentum) may be used, but there can be artifacts due to peritoneal tissue processing. Aim To investigate differences in peritoneal membranes from different parts of the peritoneum, and also 2 different fixatives, in experimental PD and a peritonitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Additionally, there is a need to establish a biopsy area and fixation method for precise morphological examination of biopsy specimens. In an earlier study on experimental PD rat models, Duman et al [10] reported that the peritoneum obtained from the anterior abdominal wall was the most affected area and that there were no significant differences between fixation with 4% formaldehyde and B5 solution. Referring to this article, we sampled the parietal peritoneum of the anterior abdominal wall near the surgical wound, and the sampling site becomes almost always the same.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Additionally, there is a need to establish a biopsy area and fixation method for precise morphological examination of biopsy specimens. In an earlier study on experimental PD rat models, Duman et al [10] reported that the peritoneum obtained from the anterior abdominal wall was the most affected area and that there were no significant differences between fixation with 4% formaldehyde and B5 solution. Referring to this article, we sampled the parietal peritoneum of the anterior abdominal wall near the surgical wound, and the sampling site becomes almost always the same.…”
Section: Discussionmentioning
confidence: 97%
“…To the best of our knowledge, only a few studies have reported on the methodology of peritoneal biopsy [7][8][9][10]. Moreover, a detailed biopsy procedure has been described in only one study [7], where the authors have proposed a suture method for collecting peritoneal samples.…”
Section: Past Reports and Issues About Peritoneal Biopsymentioning
confidence: 99%
See 1 more Smart Citation
“…Among the technical problems that have to be faced when handling animal models, tissue-sampling problems must be highlighted. The peritoneal tissue is quite fragile, dries quickly when exposed to the air and can easily be damaged even after delicate contact with surgical gloves or instruments (Duman and Sen, 2009 ). Furthermore, in patients on PD the visceral peritoneum exhibits more pronounced alterations than the parietal peritoneum, while in many of the studies conducted in animal models the biopsy samples are obtained by the parietal peritoneum.…”
mentioning
confidence: 99%